The effect of three consecutive days of time trial testing on performance measures in young and veteran cyclists - Fell, J. W.; Haseler, L. J.; Harrison, G. J. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
There is a common belief amongst athletes that a progressive decline in the speed of recovery from training and competition occurs with advancing age. Age associated declines in physiological function and athletic performance have been repeatedly confirmed within the research literature, adding support to this speculation. However, while there is some research supporting age related differences in exercise induced muscle damage and adaptive potential, much of this research has been completed on animals or sedentary humans, and has used fatigue/damage protocols that are extreme and unrealistic to most athletes. To date there is no study that has adequately compared young and aged athletes for the effects of fatigue and recovery induced by intense 'typical' exercise experienced through training or competition. The authors carried out such an examination.